"Deep phenotyping" of human myeloid derived suppressor cells from the lungs and blood of patients with tuberculosis and other lung diseases - Young, Carly (Stellenbosch : Stellenbosch University, 2019)
Thesis (MMed)--Stellenbosch University, 2019.